THE INFLUENCE OF FINANCIAL INCLUSION AND FINANCIAL LITERACY ON FINANCIAL PERFORMANCE (Case Study Of Bank Sumut Syariah Panyabungan) - Ummi Itiah Nasution; Kamilah K; Nur Ahmadi Bi Rahmani (UNIVED Press, 2024)
The purpose of this research is to find out how the financial performance of Bank Sumut Syariah Panyabungan is influenced by financial inclusion and financial literacy. In this research a questionnaire was used as a data collection tool. All employees of Bank Sumut Syariah Panyabungan who were sampled in this study were the population. Thirteen workers were used to collect samples using a saturated sampling method (also known as total sampling). Validity test, reliability test, normality test, multicollinearity test, t test, f test, and r test are the data analysis methodologies used in this study. The research findings show that there is a relationship between financial inclusion and financial performance, with a sig value of 0.041 and tcount 2.256 > ttable 2.131, there is a relationship between financial literacy and financial performance, with a sig value of 0.026 and tcount 2.486 > ttable 2.131, and a potential relationship between inclusion finance with financial performance, with a sig value of 0.002 and fcount of 9.549. The research findings show that at Bank Sumut Syariah Panyabungan, financial inclusion and literacy both have an impact on financial performance.